Rancang Bangun Sistem Informasi Manajemen Hotel Dengan Aplikasi Visual Basic Pada Homestay "The Rumah Kita" Lumajang - Hayuranistya, Corhepaticha; Setyawan, Henry Bambang; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Homestay â€œThe Rumah Kitaâ€ Lumajang, East Java which has the concept of a family inn. Curently Homestay â€œThe Rumah Kitaâ€ Lumajang has a total of 13 rooms are divided into three types. Homestay "The Home" also provides facilities to pamper guests, such as restaurant, Snack 'n Coffee shop, minimarket, meeting room, Room Service, and free wifi area. For a hotel, the speed and accuracy of the data needed to make record relating to the management of guest data, room reservations, lodging transactions, transactions additional orders (food, snack, or drink), as well as other amenities. While the administration at Homestay "The Home" still requires a lot of changes, especially for the data collection process is not computerized and centralized.Information Systems Management with Visual Basic application is expected to simplify and accelerate the recording of transactions carried out by Homestay "The Home", can manage data into information that is accurate and fast, and can improve service to guests.Â